A National Identity Framework Development: Adaptation of Indigenous Culture inModern Contemporary Architecture - Sarah Mohd Hilmee,; Kamarul Afizi Kosman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The failure of developing an architectural national identity has been highlighted by most scholars and architectural experts in Malaysia. Most architecture produced since Malaysia’s independence are influenced by imported architectural styles. Majority of the country’s architecture do not reflect the identity of its people, nor does it reflect the climate in which it is built in. Furthermore, effects of globalisation and the universalisation of architecture itself creates a plethora of issues that contribute to the lack of diversity in design, unresponsiveness to environmental concerns as well as the needs of the user. Lack of cultural heritage and national identity in architecture can be attributed to the lack of guideline or framework that allows for architects to use as a reference in designing architecture with national identity. Therefore, this study’s objective is to provide a theoretical rationale for the development of an architectural national identity framework, to identify methods of adaptation of culture and cultural elements into modern contemporary architecture and lastly to identify key factors and common values that contribute to successful architecture. This study identified 5 architecture projects that reflect an adaptation of culture in modern contemporary architecture. The study revealed that there are tangible and intangible elements that contribute to design adaptation of culture in modern contemporary architecture. The role of architecture as a bridging point can both protect, preserve, and revitalise cultural heritage as well as link the tangible and intangible elements with modern contemporary architecture. The study also suggests future opportunities for research on this topic.